Influência da sobrecarga aguda de ferro no eixo hipotálamo-hipófise-gonodal e na função cardiovascular de ratas - Rossi, Emilly Martinelli (2015)
Iron is an essential metal and plays critical role in physiologic process of mammals. However, iron overload as well their tissue deposit have been shown to be endocrine disrupters. However, studies evaluating the effects of acute iron overload on hypothalamus-pituitary-gonodal (HPG) axis health are particularly sparse. This study evaluated the acute iron overload on the HPG function, the production of free radicals and the effects on hemodynamic parameters. Females rats were treated with iron dextran (250, 500 e 1000 mg/Kg ip) and reproductive morphophysiological was assessed by histological analysis, was measured the concentration of iron by atomic spectrophotometry, oxidative stress in the pituitary, ovary and aortic segments by DHE, estrogen levels in female rats treated with iron. Treatment with iron overload triggered accumulation in tissues , increase of superoxide anion production in the pituitary , ovary and aorta, abnormal ovarian follicular development and reduction of estrogen levels and changed the PSVD observed in the group Fe 500. Together, these data provide in vivo evidence that acute iron overload are toxic for HPG morphophysiology, which may be associated with risks to reproductive function.